Adult and Adolescent Patient Evaluations of Electroconvulsive Therapy in Comparison to Other Therapeutic Modalities. Issue 1 (March 2018) - Bloch, Yuval; Linder, Muly; Kalman, Noa; Koubi, May; Gal, Gilad; Nitsan, Uriel; Maoz, Hagai; Lurie, Ido
Abstract : Objectives: There is an increasing awareness of the importance of patients' subjective evaluations of therapy. Regarding electroconvulsive therapy (ECT), the results are conflicting. We hypothesized that making a comparison between patients' satisfaction with ECT and other forms of psychiatric therapies would capture personal experience as opposed to opinion about the treatment modalities. We compared adult responses to adolescent responses. Methods: Four unmatched patient groups were recruited (N = 98) and were divided as follows: ( a ) patients treated with ECT as adolescents (n = 13), ( b ) patients treated with ECT as adults (n = 25), ( c ) patients hospitalized as adolescents but not treated with ECT (n = 30), and ( d ) patients hospitalized as adults but not treated with ECT (n = 30). All patients were interviewed using similar questions related to their satisfaction regarding the treatment modalities they experienced, including psychotherapy, pharmacotherapy, hospitalization and ECT, and years after being treated. Results: Adults and adolescents viewed ECT as a legitimate and effective form of treatment (70%). Patients who were treated with ECT had a more positive attitude toward this treatment compared with patients who had not been treated with ECT. In comparison to other treatment modalities, ECT was considered by both adolescents and adults as the least effective form of therapy. Psychotherapy was considered the most effective, specifically among adolescents. Conclusions: Comparing patients' satisfaction in regard to different therapeutic modalities can potentially help clarify discrepancies in patient reports on satisfaction with ECT. Patients' satisfaction with ECT, just like their clinical response to ECT, is more dichotomous than with other forms of therapy.